2007
DOI: 10.1029/2006ja012019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 3–7 October 2000 and 15–24 April 2002 geomagnetic storms with an optimized nonlinear dynamical model

Abstract: A computationally optimized low‐dimensional nonlinear dynamical model of the magnetosphere‐ionosphere system called WINDMI is used to analyze two large geomagnetic storm events, 3–7 October 2000 and 15–24 April 2002. These two important storms share common features such as the passage of magnetic clouds, shock events from coronal mass ejections, triggered substorms, and intervals of sawtooth oscillations. The sawtooth oscillations resemble periodic substorms but occur in association with strong or building rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…The onset of the substorm was between 03:05 and 03:10 UTC on the day . With the solar wind parameters obtained from the ACE spacecraft translated into the nose of the magnetosphere (Spencer et al, 2007), the resultant input rectified voltage is shown in the bottom panel of Fig. 3.…”
Section: Results For 31 July 1997 and 13 April 2000 Substormsmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of the substorm was between 03:05 and 03:10 UTC on the day . With the solar wind parameters obtained from the ACE spacecraft translated into the nose of the magnetosphere (Spencer et al, 2007), the resultant input rectified voltage is shown in the bottom panel of Fig. 3.…”
Section: Results For 31 July 1997 and 13 April 2000 Substormsmentioning
confidence: 99%
“…The WINDMI model is described in some detail in , Spencer et al (2007) and more recently in Patra et al (2011). The equations of the model are given by the following:…”
Section: Windmi Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma physics‐based WINDMI model uses the solar wind dynamo voltage V sw generated by a particular solar wind‐magnetosphere coupling function to drive eight ordinary differential equations describing the transfer of power through the geomagnetic tail, the ionosphere and the ring current. The WINDMI model is described in some detail by Doxas et al [2004], Horton et al [2005] and more recently by Spencer et al [2007]. The equations of the model are given by The largest energy reservoirs in the magnetosphere‐ionosphere system are the plasma ring current energy W rc and the geotail lobe magnetic energy W m formed by the two large solenoidal current flows ( I ) producing the lobe magnetic fields.…”
Section: Windmi Model Descriptionmentioning
confidence: 99%
“…However an optimized linear scale yields better results of λ AL than the fixed scale which does not take into account changes in width, height, and location of the electrojet during geomagnetic activity. The scaling factor for the 3–7 October 2000 storm was calculated to be 3275, while for the 15–24 April 2002 storm it was computed to be 2638, both in A / nT [ Spencer et al , 2007].…”
Section: Windmi Model Descriptionmentioning
confidence: 99%